Diverse mixtures of 2, 4-dihydroxy tautomers and O4 protonated conformers of uridine and 2′-deoxyuridine coexist in the gas phase1. Issue 39 (21st October 2015) - Wu, R. R.; Yang, Bo; Frieler, C. E.; Berden, G.; Oomens, J.; Rodgers, M. T.
<x xml:space="preserve">Abstract</x> IRMPD spectroscopy and theoretical studies reveal that a diverse mixture of minor 2, 4-dihydroxy and O4 protonated tautomeric conformations of the protonated forms of uridine and 2′-deoxyuridine are populated by ESI.